2020
DOI: 10.20525/ijrbs.v9i5.759
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of lecturers’ demographic factors affecting research performance in Indonesia

Abstract: This study aims to determine the demographic factors that affect lecturer publication performances in Indonesia. This study employs data from 658 lecturers in the faculties of economics and business from 7 universities in Indonesia. Data of lecturer profile consisting of academic rank, administrative position, highest education, the country where lecturers received their degrees (overseas or regional), age, work years, and gender was collected from the Ministry of Research online database. To find out the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several studies have shown that certain parameters like research output (bibliometric measures) [37, 44.] job satisfaction and academic productivity [45] vary in relation to academic ranking. For example, a positive relationship was recorded between academic ranking and the output of scienti c publications using different indexes such as SINTA (National online database system in Indonesia) and h-index [37,44].…”
Section: Adaptive Expertise and Academic Rankmentioning
confidence: 99%
“…Several studies have shown that certain parameters like research output (bibliometric measures) [37, 44.] job satisfaction and academic productivity [45] vary in relation to academic ranking. For example, a positive relationship was recorded between academic ranking and the output of scienti c publications using different indexes such as SINTA (National online database system in Indonesia) and h-index [37,44].…”
Section: Adaptive Expertise and Academic Rankmentioning
confidence: 99%
“…The other effectiveness variables are academic position, publications, lecturer's workload, certification, lesson plan, and assessment guidelines. The academic position is closely related to publication [30]. The publication is about scientific performance, so the higher the academic position, the more the number of publications [30], [31].…”
Section: Model Formingmentioning
confidence: 99%
“…The academic position is closely related to publication [30]. The publication is about scientific performance, so the higher the academic position, the more the number of publications [30], [31]. The number of publications is one of the indicators of research productivity.…”
Section: Model Formingmentioning
confidence: 99%
“…Even though there is a decline in political dominance since early 2000 [ 15 , 16 , 17 ], the academician’s ethos is almost unaffected in the last twenty years [ 18 ], especially in the legal disciplines. Scientific legal research repeats the old tradition of bringing forwards respect and decencies rather than critics and theoretical analyses.…”
Section: Introductionmentioning
confidence: 99%